2005
DOI: 10.5713/ajas.2005.728
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Bovine Lymphoma Caused by Bovine Leukemia Virus Infection in Holstein-Friesian Dairy Cattle in Korea

Abstract: However, few studies have been performed on lymphoma, the clinical form of EBL, until now (Lim, 1969;Lee et al., 1982), and the reports on characteristics of lymphoma in the naturally BLV-infected cattle are limited in Korea. It is the purpose of this study to assess the frequency and distribution of lymphoma in the BLV-infected cattle. MATERIALS AND METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…The present study revealed high incidence in male cattle (75%) than in female (25%) cattle, which was in agreement with the reports of Singh [15,16] in buffaloes. In contrary, Yoon et al [14] observed 100% of the lymphosarcoma cases in female cattle. In the present study, the enlargement was observed mostly in lymph nodes followed by the visceral organs, as observed by Yoon et al [14] Sabareeswaran et al [17] and Anusha et al [18] reported cases of ocular lymphoma, pulmonary lymphoma, uterine lymphosarcoma respectively in buffaloes.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The present study revealed high incidence in male cattle (75%) than in female (25%) cattle, which was in agreement with the reports of Singh [15,16] in buffaloes. In contrary, Yoon et al [14] observed 100% of the lymphosarcoma cases in female cattle. In the present study, the enlargement was observed mostly in lymph nodes followed by the visceral organs, as observed by Yoon et al [14] Sabareeswaran et al [17] and Anusha et al [18] reported cases of ocular lymphoma, pulmonary lymphoma, uterine lymphosarcoma respectively in buffaloes.…”
Section: Discussionmentioning
confidence: 90%
“…In contrary, Yoon et al [14] observed 100% of the lymphosarcoma cases in female cattle. In the present study, the enlargement was observed mostly in lymph nodes followed by the visceral organs, as observed by Yoon et al [14] Sabareeswaran et al [17] and Anusha et al [18] reported cases of ocular lymphoma, pulmonary lymphoma, uterine lymphosarcoma respectively in buffaloes. Lymph might be the main route of metastasis to different organs as mentioned by Yoon et al [14].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Los insectos hematófagos actúan como vectores de la enfermedad, y a pesar de que no es muy habitual la transmisión vertical, intrauterina o calostral (OIE, 2011) podría provocar en un predio infectado un mayor porcentaje de animales enfermos, con las consecuentes pérdidas econó-micas para el productor. En estudios realizados en Corea en 30 animales enfermos con LEB, se observaron tejidos neoplásicos en los ganglios linfáticos de todos los animales; también se observaron nódu-los en intestino (96,4 %), corazón (88,9 %), estóma-go (73,1 %) y diafragma (62,5 %), sugiriendo que se produce metástasis de la enfermedad (Yoon et al, 2005). Por lo tanto, es necesario un mayor control de LEB con la finalidad de monitorear y dar seguimiento a los animales, principalmente en los más jó-venes, ya que representan mayor riesgo para la producción.…”
Section: Introductionunclassified